O processo de fabricação da farinha de mandioca (manihot esculenta crantz) com ênfase na comercialização e aplicação da função afim - FERREIRA, Patrícia Ferreira e (2023)
The present work, in addition to addressing the historical importance of cassava, describes the process of making flour in the quilombola community Nossa Senhora de Nazaré, located in the Itacuruçá River-Alto Ilhas de Abaetetuba, with emphasis on the commercialization and application of the related function. In this sense, the research has as its general objective, firstly, the understanding of the cassava flour manufacturing process and the possible contributions that this function can bring, from the modeling of problems related to obtaining flour profits. As a methodology, field research was carried out with farmers from the aforementioned community, through a questionnaire, in addition to searches in academic works. Thus, we sought to demonstrate the relationship between theoretical and practical knowledge, through a descriptive research based on primary and secondary sources and qualitative and quantitative data approach.